2014
DOI: 10.1016/j.enconman.2014.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Process simulation of co-firing torrefied biomass in a 220MWe coal-fired power plant

Abstract: This version is available at https://strathprints.strath.ac.uk/53526/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 25 publications
3
29
0
2
Order By: Relevance
“…It is a process that is considered to improve the logistics of the upgraded fuel [6,7] and make it more suitable for final use such as co-firing [8][9][10] or gasification [11][12][13][14]. Torrefaction is sometimes called slow pyrolysis and it typically takes place at temperatures between 250 and 300°C with residence times ranging between 10 and 60 min [5,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It is a process that is considered to improve the logistics of the upgraded fuel [6,7] and make it more suitable for final use such as co-firing [8][9][10] or gasification [11][12][13][14]. Torrefaction is sometimes called slow pyrolysis and it typically takes place at temperatures between 250 and 300°C with residence times ranging between 10 and 60 min [5,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Tsalidis et al [49], for example, demonstrate the benefits of torrefied biomass use in coal-fired power generation plants in the Netherlands. In 2012, Li et al [50] using process simulation software (Aspen Plus) and analyzing the possibility of co-firing torrefied biomass in a 220 MWe coal-fired power plant concluded that 100% torrefied biomass usage with maximum efficiency and minimum emissions is technically possible. Huang et al [51] and Basu et al [52] demonstrate environmental benefits using torrefaction in power plant in Taiwan and in the eastern Canada respectively.…”
Section: Technical Possibilities Of Torrefied Biomass Consumption In mentioning
confidence: 99%
“…Para el software Aspen Plus, la biomasa se considera un compuesto "no convencional", por lo tanto para simular el proceso de gasificación usando los algoritmos y subrutinas incluidas por defecto en el software, es necesario descomponerla en compuestos reactivos (de acuerdo a su análisis próximo y análisis último) antes de ingresarla al gasificador. Para tal efecto se utiliza un reactor de rendimiento (bloque R-YIELD) con ayuda de subrutinas en FORTRAN [12,18]. En la Figura 3 se muestra el modelo utilizado para simular el proceso de gasificación.…”
Section: Descripción Del Modelounclassified